Efficacy of Visual inspection with acetic acid (VIA) and PAP smear as a screening method for diagnosis of premalignant lesions of cervix in high-risk patient - Lokhande, Supriya; Neethika Raghuwanshi,; Madhuri Dhakne,; Sushma Deshmukh, (Asian Journal of Medical Sciences, 2022)
Background: Carcinoma Cervix is one of the common malignant pathology causing considerable morbidity and mortality in women. One of the important aspects of management of carcinoma cervix is its early detection and appropriate management since delay in the diagnosis can have catastrophic consequences. Unfortunately in developing countries in many cases, diagnosis is delayed due to non-availability of facilities at rural areas. To overcome this screening methods such as Visual Inspection with Acetic Acid (VIA) and PAP smear can be done in high-risk patients and in selected cases cervical biopsy can be done. Aims and Objectives: (1) To compare VIA and PAP smear in relation to colposcopy as a screening method for premalignant lesions of cervix. (2) To study the efficacy of VIA as a primary screening test for detection of premalignant lesions of cervical cancer. Materials and Methods: This was a prospective analytical study in which 100 women with unhealthy cervix attending obstetrics and gynecology out patient department who were willing to participate and gave written informed consent were enrolled in the study on the basis of a predefined inclusion and exclusion criteria. VIA was done. Pap smear was taken and slides were stained with modified Papanicolaou staining method and examined under light microscope. we compared the efficacy of VIA and PAP smear as a screening method for diagnosis of premalignant lesions of cervix in high-risk patient, and the results were confirmed with the help of colposcopy examination and its histopathological correlation with guided biopsy. Results: Mean age of the study population was found to be 40.94 years. When VIA, PAP Smear, and colposcopy were compared highest sensitivity was seen in VIA whereas colposcopy showed highest accuracy (82%). PAP was found to have a higher specificity (84.62%) as compared to VIA or colposcopy. Highest positive predictive value and negative predictive value was seen in PAP smear (78.95%) and colposcopy (86.96%). Conclusion: VIA is an easy to perform and highly sensitive test for diagnosis of carcinoma cervix however it has got a poor specificity. Colposcopy was found to be a better diagnostic test as it was both more sensitive as well as specific to diagnose premalignant lesions.